Examining user comments for deliberative democracy: a corpus-driven analysis of the climate change debate online - Collins, Luke C.; Nerlich, Brigitte (Taylor & Francis, 2014)
The public perception of climate change is characterized by heterogeneity, even polarization. Deliberative discussion is regarded by some as key to overcoming polarization and engaging various publics with the complex issue of climate change. In this context, online engagement with news stories is seen as a space for a new “deliberative democratic potential” to emerge. This article examines aspects of deliberation in user comment threads in response to articles on climate change taken from the Guardian. “Deliberation” is understood through the concepts “reciprocity”, “topicality”, and “argumentation”. We demonstrate how corpus analysis can be used to examine the ways in which online debates around climate change may create or deny opportunities for multiple voices and deliberation. Results show that whilst some aspects of online discourse discourage alternative viewpoints and demonstrate “incivility”, user comments also show potential for engaging in dialog, and for high levels of interaction.